PENETAPAN DALUARSANYA PENUNTUTAN OLEH PENEGAK HUKUM POLRI-JAKSA PENENTUT UMUM DALAM PERKARA PIDANA PEMALSUAN TANDA TANGAN PERMOHONAN PENETAPAN AHLI WARIS - Siagian, Natalin (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTWith the entry into force of criminal law in Indonesia, the legal rights and obligations of a person who commits a violation or a crime that is against the law must be subject to an examination in the court to determine whether a person charged with a crime is proven to have committed accountable for his actions.The Criminal Code (KUHP) has stipulated a certain period of time regarding the problem of prosecution, can be expired according to law. The provisions in article 78 of the Criminal Code actually regulate the expiration of criminal prosecution rights, but also need to be related to the right to carry out the sentence. At the time of the death of the right to carry out a sentence longer than the death of the criminal prosecution because the defendant's mistake was certain.For the sake of ensuring legal certainty, it should be evidenced regarding the forgery of signatures on the letter applied as in accordance with existing criminal laws.